Perancangan Strategi E-Business Untuk Mendukung Kemajuan Bisnis Kuliner Di Home Industri - Juni Anggrainy; Lenita Selviana; Suci Afria Sasty Siregar; Nurbaiti Nurbaiti (Journal of Creative Student Research, 2023)
This study aims to determine the design of e-business strategies, especially in the culinary field in the Home Industry. Currently,many small and medium entrepreneurs use internet technology to increase their competitive advantage in selling culinary businesses. One popular strategy is the use of e-business, such as Facebook, WhatsApp, and Instagram to improve the performance of business operations. However,to implement an e-business strategy, sellers needa model that can attract customers so that they can generate profits. In this study the authors used a theoretical approach which only describes theories as a basis for thinking and literary methods in which this research method retrieves data from a collection of articles, journals and books from all forms of related sources. The author obtains results from research showing that E-Bussines Home Industry is able to generate promising profits and can compete and innovate to produce new products and have high selling value for the progress of Home Industry businesses, especially in the culinary field,now and in the future.